2012
DOI: 10.1159/000338491
|View full text |Cite|
|
Sign up to set email alerts
|

RNA Interference of PARG Could Inhibit the Metastatic Potency of Colon Carcinoma Cells via PI3-Kinase/Akt Pathway

Abstract: Aims: To investigate the role and mechanism of PARG inhibition of metastatic behavior in colonic carcinoma cells. Methods: We examined the effects of PARG protein knockdown by RNA interference on invasion, migration and matrix adhesion of colon carcinoma cell lines in vitro and using a murine in vivo model of liver metastasis. Metastasis related genes were detected using mRNA and protein levels. Moreover, LY294002, an Akt phosphorylation inhibitor, was used to determine whether the suppression of metastatic be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Nevertheless, these results strengthen the notion that targeting the Ras/PI3K/PTEN/Akt/ mTOR pathway, also via INSR inhibition, is gaining wider scientific consent in cancer therapy (Pollak, 2008;Pollak, 2012a;Li et al, 2012). Moreover, the Akt analogue Sgk1 appears a key factor for colon adenocarcinoma in vitro proliferation (Towhid et al, 2013).…”
Section: Discussionsupporting
confidence: 60%
“…Nevertheless, these results strengthen the notion that targeting the Ras/PI3K/PTEN/Akt/ mTOR pathway, also via INSR inhibition, is gaining wider scientific consent in cancer therapy (Pollak, 2008;Pollak, 2012a;Li et al, 2012). Moreover, the Akt analogue Sgk1 appears a key factor for colon adenocarcinoma in vitro proliferation (Towhid et al, 2013).…”
Section: Discussionsupporting
confidence: 60%
“…Matrix metallopeptidase 9 (MMP9) is an important matrix proteinase that degrades collagen type IV, the major component of the basement membrane [7][8][9][10]. Overexpression of MMP9 often facilitates metastatic spread of various tumors, including BC [11][12][13][14][15][16], and appears to be one of the most important molecules to directly promote cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies had also showed that PARP-1 inhibition can dramatically decrease the activation of nuclear factor-kB and its DNA-binding activity (Li et al, 2009, Li et al, 2012. PARP-1 has been reported to be a co-activator of NF-kB in many inflammatory disorders (Pétrilli et al, 2004;Zheng et al, 2004).…”
Section: Discussionmentioning
confidence: 93%
“…NF-kB is a transcription factor that participates in diverse processes such as immunity, inflammation, cell proliferation, apoptosis or embryonal development (Fauzee et al, 2010;Fauzee et al, 2012;Li et al, 2012) Active NF-kB consist of dimeric combination of members of the NF-kB/Rel transcription factor family (Rothwarf and Karin, 1999).…”
Section: -Aminoisoquinolinone Reduces the Expression Of Vascularmentioning
confidence: 99%